What is The Correlation Between Chemical Engineering and Special Needs Education from The Perspective of Bibliometric Analysis Using VOSviewer Indexed by Google Scholar - Mohd Dzul Hakim Wirzal; Zulfan Adi Putra (Universitas Pendidikan Indonesia (UPI), 2022)
Chemical engineering is a field of study that focuses on increasing the values of one form of material to the other via chemical processes. Its typical activities cover research and development, feasibility studies, engineering designs, plant operations, and improving plant performances. The goal of this research is to analyze “Chemical Engineering Special Needs” by combining mapping analysis and the VOSviewer app. The Publish or Perish app is also used to support and find articles that are relevant to keywords used for searching. Thus,